Characteristics of thermophysical parameters in the Wugongshan area of South China and their insights for geothermal genesis - Liu, Kai; Zhang, Yaoyao; He, Qingcheng; Zhang, Shouchuan; Jia, Wuhui; He, Xiaolong; Zhang, Haoran; Wang, Luyao; Wang, Shuxun (Frontiers in Environmental Science, 2023)
The Wugongshan area is rich in medium-low temperature convective geothermal resources, among which there are more than 10 geothermal fields in Wentang, Wanlongshan, Wenjia, Hongjiang, etc. There are few basic geothermal geological researches in the geothermal fields and their peripheral areas, so far no systematic research work of thermophysical parameters has been carried out. In this paper, 85 rock samples were collected from the surface and boreholes, covering the strata and magmatic rocks in the study area. The results show that: The average radioheat generation rate, the average thermal conductivity and the average specific heat are 0.24-5.49 (μW/m3), 1.995-4.390 (W/mK), 1.318-4.829 (MJ/m3K), respectively. The average thermal diffusivity ranges from 1.115 to 1.611×10-6m2/s. The highest radioheat generation rate is Jurassic granite and the lowest is quartz vein. The largest thermal conductivity and specific heat is the siliceous quartzite and the smallest is the quartz vein. The highest thermal diffusivity is Cambrian metamorphic mica schist, and the lowest is siliceous quartzite. The radioactive heat generation rate, thermal conductivity, specific heat and thermal diffusivity are closely related to the chemical composition, mineral composition, rock fabric, porosity, water content and temperature and pressure conditions of rocks in the whole area. There is a linear relationship between thermal conductivity (K) and thermal diffusivity (κ), and the correlation equation is K=-0.3144k + 3.2172. Combined with the characteristics of thermophysical parameters, the genetic theory of deep crust heat generation + structural heat accumulation + siliceous quartzite heat conduction + granite heat preservation is preliminarily proposed.